ENCOMPASSING HIGH-PROFICIENT STUDENTS IN HELPING LOW-PROFICIENT STUDENTS IN LEARNING ENGLISH IN INDONESIAN ENGLISH PRIMARY CLASSESTITLE IN ENGLISH - Susanto, Indra; Halum, Yustus Sentus (Universitas Muhammadiyah Makassar, 2024)
Copland et al. (2014) report that a large number of teachers deal with students at various phases of learning and with diverse individual requirements; students are frequently viewed as weak in language learning. This paper tries to find out the answer to how can teachers involve the high-proficient students in supporting low-proficient students in Indonesian English primary classes? The investigation of this topic can provide English teachers with strategies for encouraging student interactions between students of varying English proficiency levels. In addition, it provides a variety of techniques for maximizing the English learning experience for pupils of varying proficiency levels. In this paper, it is argued that incorporating positive interaction throughout the learning process is beneficial for the support of low-proficient students by high-proficient students in Indonesian English primary classes. Some of the ways it can be achieved is through peer learning, cooperative learning, and digital learning, among other methods. Our curriculum may require consideration of positive student interaction and the inclusion of materials on incorporating positive student interaction in English language learning through various Teacher Professional Development program methodologies. Additionally, Elementary English teachers in Indonesia should master teaching techniques that integrate positive student interactions.